Putting the Federal Archives to cultural use in research and teaching - Griffin, Stanley ([s.n.] [S.l.], 2006)
Seeks to show that the existence of the British West Indian Federation was the defining moment in the Caribbean's history for it established the framework for greater inter-regional cultural exchanges and expressions.